Carbapenem Resistant Aeromonas hydrophila Carrying blacphA7 Isolated From Two Solid Organ Transplant Patients - Hilt, Evann E.; Fitzwater, Sean Patrick; Ward, Kevin; de St. Maurice, Annabelle; Chandrasekaran, Sukantha; Garner, Omai B.; Yang, Shangxin (Frontiers in Cellular and Infection Microbiology, 2020)
Aeromonas hydrophila resides in a variety of aquatic environments. Infections with A. hydrophila mainly occur after contact with fresh or brackish water. Nosocomial infections with A. hydrophila can also occur. A. hydrophila infections can be difficult to treat due to both intrinsic and acquired antimicrobial resistance (AMR) mechanisms. In 2018-19, we isolated multi-drug resistant (MDR) A. hyrodphila from two solid organ transplant patients with intra-abdominal infections. We aimed to characterize their AMR mechanisms and to determine their genetic relatedness to aid epidemiological investigation. We performed whole genome sequencing (WGS) using Illumina MiSeq and Nanopore MinIon on 3 A. hydrophila isolates, with one isolate from Patient A (blood) and two isolates from Patient B (abdominal and T-tube fluid, isolated 2 weeks apart). Phenotypic assays included: Broth Microdilution (BMD), Modified Hodge Test (MHT), Modified Carbapenem Inactivation Method (mCIM) and EDTA Carbapenem Inactivation Method (eCIM). Data analyses were performed using CLCbio and Geneious. AMR genomic analysis revealed that all three isolates possess chromosomally encoded genes including blaOXA-12 (oxacillinase), blacepS (AmpC), and blacphA7 (metallo-beta-lactamase). All isolates tested strongly positive by MHT and mCIM, but only Patient B’s second isolate (after 2 weeks of meropenem treatment) tested positive by eCIM. More intriguingly, Patient B’s first isolate (before meropenem treatment) tested falsely susceptible to carbapenems by BMD, suggesting blacphA7 gene was not expressed constitutively. Phylogenetic analysis showed the two isolates from Patient B were highly similar with only 1 SNP difference. The isolate from Patient A only differed from Patient B’s isolates by 35 and 36 SNPs, respectively, suggesting close genetic relatedness. Further epidemiological investigation is undergoing. We report the first cases of CphA-mediated carbapenem resistant A. hydrophila in the U.S. It is concerning that 1 out of 3 isolates tested falsely susceptible to carbapenems by BMD despite clear carbapenemase production shown by strongly positive MHT and mCIM. In both cases, meropenem was initially used to treat the patients. Clinicians and microbiologists in the US should be aware of the emerging MDR Aeromonas nosocomial infections and the potential false carbapenem susceptible results due to CphA-type carbapenemase, which may be induced during treatment.